"After the massacre of illusions": Specters of the GDR in the work of Volker Braun - Leeder, K (Duke University Press, 2012)
The German Democratic Republic (GDR) was founded on the specter of communism; it now haunts contemporary capitalism as unrealized aspiration, trauma, or travesty. This article focuses on the representation of the after-life of the GDR in the work of Volker Braun. It examines the dominant concern with mortality, death, revenants, and specters in his recent work, especially Tumulus (1999) and Auf die schönen Possen (Here's to the Good Times, 2005). This concern is read against broader international interests in lateness, old age, specters, and “hauntology,” gesturing especially toward Jacques Derrida's Specters of Marx (1994). Traditionally, a ghost is seen as a sign of unfinished business: a disturbance in the symbolic, moral, or epistemological order that can be resolved once the ghost has delivered its message and fulfilled its mission. However, Braun's specters simultaneously function as symptoms of a profound contemporary crisis: in mobilizing unaccommodated, unrealized, or taboo aspects of the GDR past, but also in presenting an aesthetic opportunity in that they “recall” the various intertexts they cite (from Hamlet to Karl Marx or the medieval danse macabre) and militate against amnesia or the fetishization of the real. The article concludes by asking what the return of the dead in Braun's work means for the Berlin Republic.